Oral Bacteriotherapy Reduces the Occurrence of Chronic Fatigue in COVID-19 Patients - Santinelli, Letizia; Laghi, Luca; Innocenti, Giuseppe Pietro; Pinacchio, Claudia; Vassalini, Paolo; Celani, Luigi; Lazzaro, Alessandro; Borrazzo, Cristian; Marazzato, Massimiliano; Tarsitani, Lorenzo; Koukopoulos, Alexia E.; Mastroianni, Claudio M.; et al. (Frontiers in Nutrition, 2022)
Long COVID refers to patients with symptoms as fatigue, “brain fog,” pain, suggesting the chronic involvement of the central nervous system (CNS) in COVID-19. The supplementation with probiotic (OB) would have a positive effect on metabolic homeostasis, negatively impacting the occurrence of symptoms related to the CNS after hospital discharge. On a total of 58 patients hospitalized for COVID-19, 24 (41.4%) received OB during hospitalization (OB+) while 34 (58.6%) taken only the standard treatment (OB–). Serum metabolomic profiling of patients has been performed at both hospital acceptance (T0) and discharge (T1). Six months after discharge, fatigue perceived by participants was assessed by administrating the Fatigue Assessment Scale. 70.7% of participants reported fatigue while 29.3% were negative for such condition. The OB+ group showed a significantly lower proportion of subjects reporting fatigue than the OB– one (p < 0.01). Furthermore, OB+ subjects were characterized by significantly increased concentrations of serum Arginine, Asparagine, Lactate opposite to lower levels of 3-Hydroxyisobutirate than those not treated with probiotics. Our results strongly suggest that in COVID-19, the administration of probiotics during hospitalization may prevent the development of chronic fatigue by impacting key metabolites involved in the utilization of glucose as well as in energy pathways.